2016
DOI: 10.1016/j.matdes.2015.10.119
|View full text |Cite
|
Sign up to set email alerts
|

Localized microstructural characterization of a dissimilar metal electron beam weld joint from an aerospace component

Abstract: Hydrogen induced cold cracking (HICC) and hydrogen embrittlement (HE) are influenced by the microstructural evolution, residual plastic strain (i.e. local misorientation), recrystallization of grains and the resultant grain boundary characteristic distribution (GBCD) brought about by welding processes. HICC and HE are known to cause failures in aerospace components and it is vitally important to quantify the microstructural evolution, degree of residual plastic strain and determine the GBCD across dissimilar w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 55 publications
(65 reference statements)
0
10
0
Order By: Relevance
“…A decrease in strain rate increases the time duration of the test, which will increase the amount and depth of hydrogen diffusion into the sample specimen and this corresponds to the amount of subsurface cracks observed. and more details about it can be found elsewhere ( Jothi et. al.…”
Section: Sem Fractography Of Alloy 718 Failed Specimensmentioning
confidence: 99%
“…A decrease in strain rate increases the time duration of the test, which will increase the amount and depth of hydrogen diffusion into the sample specimen and this corresponds to the amount of subsurface cracks observed. and more details about it can be found elsewhere ( Jothi et. al.…”
Section: Sem Fractography Of Alloy 718 Failed Specimensmentioning
confidence: 99%
“…Inconel 718 alloy is a widespread equiaxed nickel-based alloy characterized by high strength and excellent corrosion resistance, within a working temperature range between -250 and 800 . However, it is known to be susceptible to hydrogen embrittlement effects when exposed to elevated hydrogen concentrations [1,2,3,4,5]. Hydrogen can penetrate into the material during manufacturing processes or during service exposure to hydrogen-rich environments the surrounding environment during service exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen can penetrate into the material during manufacturing processes or during service exposure to hydrogen-rich environments the surrounding environment during service exposure. In the case of aerospace applications, hydrogen can arise from fuel in rocket engines and its embrittlement effects were deeply studied [5].…”
Section: Introductionmentioning
confidence: 99%
“…Panda put forward a hybrid optimization technique namely Neuro-Grey Modeling which carries out the parameter design and optimization of multi-machining characteristics of WEDM process and concluded that the model was reliable and can be implemented fast when compared with genetic algorithm [32]. It has been reported that the localized microstructural parameters such as phase distribution, grain size, distribution & grain structure also plays an important role on the effect of process parameters [35][36][37][38][39][40][41][42]. It also has been reported that the machine learning based ANN model has been used to predict the mechanical properties of metals & alloys [33,34,43].…”
Section: Introductionmentioning
confidence: 99%